2018
DOI: 10.15537/smj.2018.3.22331
|View full text |Cite
|
Sign up to set email alerts
|

Follicular aspiration versus coasting for ovarian hyper-stimulation syndrome prevention

Abstract: Objectives:To compare follicular reduction prior to human chorionic gonadotropin (HCG) trigger and coasting in terms of ovarian hyper-stimulation syndrome (OHSS) reduction, pregnancy, and cancellation rates in in vitro fertilization/ intracytoplasmic sperm injection (IVF/ICSI) cycles.Methods:This study was designed as a prospective study. The setting was the IVF unit at King Abdulaziz Medical City, Riyadh, Kingdom of Saudi Arabia. A total of 39 patients undergoing IVF/ICSI cycles, who were at risk of OHSS, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Also, Kailasam et al [25] prospectively, found coasting for 6 days with subsequent blastocyst transfer may be an effective strategy for patients at risk of OHSS with no detrimental effects on blastocyst development or live birth outcome Concerning comparative study for coasting and follicular aspiration as preventive strategy for OHSS, D'Angelo et al [25] reviewed literature for RCT assessing the efficacy of coasting versus unilateral follicular aspiration and documented that data were not pooled due to heterogeneity. Moreover, review of recently published articles detected only one study compared the effect of coasting versus aspiration on incidence of OHSS; however, that study reported no difference between follicular reduction prior to HCG and coasting, in terms of OHSS reduction as a primary endpoint [26], these results are contradictory to the result of the current study and this difference could be attributed to multiple imitations of Bushaqer's study [26], firstly, the sample size is small; 39 women were divided into two study groups and 8 women developed OHSS; 6 versus 2 women in each group, respectively but these numbers could not reach the appropriate limit for statistical analysis to be significant or non-significant. Secondly, Bushaqer's study [26] did not comment on the frequencies of OHSS severity manifestations, which are more important than the sole frequency of OHSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Kailasam et al [25] prospectively, found coasting for 6 days with subsequent blastocyst transfer may be an effective strategy for patients at risk of OHSS with no detrimental effects on blastocyst development or live birth outcome Concerning comparative study for coasting and follicular aspiration as preventive strategy for OHSS, D'Angelo et al [25] reviewed literature for RCT assessing the efficacy of coasting versus unilateral follicular aspiration and documented that data were not pooled due to heterogeneity. Moreover, review of recently published articles detected only one study compared the effect of coasting versus aspiration on incidence of OHSS; however, that study reported no difference between follicular reduction prior to HCG and coasting, in terms of OHSS reduction as a primary endpoint [26], these results are contradictory to the result of the current study and this difference could be attributed to multiple imitations of Bushaqer's study [26], firstly, the sample size is small; 39 women were divided into two study groups and 8 women developed OHSS; 6 versus 2 women in each group, respectively but these numbers could not reach the appropriate limit for statistical analysis to be significant or non-significant. Secondly, Bushaqer's study [26] did not comment on the frequencies of OHSS severity manifestations, which are more important than the sole frequency of OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, review of recently published articles detected only one study compared the effect of coasting versus aspiration on incidence of OHSS; however, that study reported no difference between follicular reduction prior to HCG and coasting, in terms of OHSS reduction as a primary endpoint [26], these results are contradictory to the result of the current study and this difference could be attributed to multiple imitations of Bushaqer's study [26], firstly, the sample size is small; 39 women were divided into two study groups and 8 women developed OHSS; 6 versus 2 women in each group, respectively but these numbers could not reach the appropriate limit for statistical analysis to be significant or non-significant. Secondly, Bushaqer's study [26] did not comment on the frequencies of OHSS severity manifestations, which are more important than the sole frequency of OHSS. On the other hand, the current study reported significantly reduced OHSS manifestations, both as frequency and severity, with follicular aspiration than with coasting, so the current study approved the efficacy and safety of follicular aspiration in comparison to coasting despite of proved efficacy of coasting.…”
Section: Discussionmentioning
confidence: 99%